Studies on the Loading and Release of Metformin HCl Using Hydrogels with EGDMA and MBA as Crosslinkers - Ariyaldi, Ariyaldi; Nizardo, Noverra Mardhatillah; Lestari, Maria Lucia Ardhani Dwi (Universitas Gadjah Mada, 2025)
Hydrogel poly(N-vinylcaprolactam-co-2-(dimethylamino)ethylmethacrylate) or (P(NVCL-co-DMAEMA)) containing the active drug metformin HCl were synthesized using the free radical polymerization method in the presence of DMAEMA and NVCL monomers by using two different crosslinkers: ethylene glycol dimethacrylate (EGDMA) and methylene bisacrylamide (MBA). FTIR spectra confirmed the successful formation of hydrogel and its loading with metformin HCl. SEM analysis revealed the physical shape and surface features. Regarding physical appearance, the texture of the hydrogel is sticky and elastic. When the hydrogel was immersed in a solution, it swelled, and returned to its original shape after drying. Additionally, the chemical degradation temperature is thermally stable at 329.75 °C. The loading test results showed that the active drug in EGDMA was 18.38 (% w/w) and 26.19 (% w/w) in MBA as crosslinkers, loaded within 24 h. The drug-loaded hydrogel containing EGDMA as crosslinkers in pH 7.4 had the highest drug release in 24 h compared to MBA. Then, the drug released from hydrogel with EGDMA in pH 2 had the highest drug release than MBA within 30 min. The P(NVCL-co-DMAEMA) hydrogel has the potential for a drug delivery system. However, additional optimizations are necessary to improve the efficiency of the hydrogels as a carrier.